2015
DOI: 10.1016/j.bspc.2014.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Resting tremor classification and detection in Parkinson's disease patients

Abstract: Parkinson is a neurodegenerative disease, in which tremor is the main symptom. This paper investigates the use of different classification methods to identify tremors experienced by Parkinsonian patients. Some previous research has focussed tremor analysis on external body signals (e.g., electromyography, accelerometer signals, etc.). Our advantage is that we have access to sub-cortical data, which facilitates the applicability of the obtained results into real medical devices since we are dealing with brain s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…The medicines used for PD treatments mainly hold back nerve impulses to control movements. The surgical or invasive methods like Pallidotomy, Deep Brain Stimulation (DBS) [5,6,7] are used to stimulate brain cells through placing electrical probes inside the brain. But both the medicines and surgeries have side effects.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The medicines used for PD treatments mainly hold back nerve impulses to control movements. The surgical or invasive methods like Pallidotomy, Deep Brain Stimulation (DBS) [5,6,7] are used to stimulate brain cells through placing electrical probes inside the brain. But both the medicines and surgeries have side effects.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…This last option can be of interest as it can improve the tremor detection. It has been previously shown that there appear to be different types of Parkinson's Disease [3]. It may well be therefore that the threshold is linked to the disease classification.…”
Section: Defuzzification and Thresholdingmentioning
confidence: 99%
“…Mainly, the diagnosis of typical cases is depend on symptoms, with the use of some tests such as neuroscience to exclude other diseases. Even though, there is no cure for Parkinson's disease [9,10]. The Primary treatments are usually with levodopa antiparkensonian, with once can used dopamine stimuli becomes less effective levodopa.…”
Section: Introductionmentioning
confidence: 99%